Assessment of Radiation Dose During Computed Tomography Examinations in a Tertiary Healthcare Facility in South-West Nigeria - Mercy Eneze Omeiza; Rachel Ibhade Obed; Abiola Olawale Ilori (Radioprotection, 2026)
Computed tomography (CT) contributes substantially to medical radiation exposure, making routine dose monitoring and optimization necessary. This study assessed radiation dose indices for adult head, chest, and abdominal CT examinations at Ekiti State University Teaching Hospital, Ado-Ekiti, Nigeria, and derived preliminary local diagnostic reference levels (LDRLs). A retrospective review covered 60 examinations, with 20 examinations in each anatomical group. Volume CT dose index (CTDIvol) and dose-length product (DLP) were obtained from the scanner console, and the 75th percentile values were used to derive the LDRLs. Effective dose was estimated from DLP using region-specific conversion coefficients. Mean CTDIvol values were 40.06 ± 18.42 mGy for head, 18.90 ± 8.15 mGy for chest, and 17.29 ± 6.32 mGy for abdomen. Mean DLP values were 960.56 ± 220.8, 662.36 ± 296.4, and 714.47 ± 196.2 mGy·cm, respectively. Estimated mean effective doses were 2.02, 9.27, and 10.72 mSv. Head CT was within the European reference values used for comparison. Chest CT exceeded the reference values for CTDIvol and DLP, while abdominal CT exceeded the DLP reference value. The derived LDRLs provide an institutional baseline for dose review and protocol optimization.